Increasing teacher professionalism through learning innovative, creative and effective at Aisyiyah Boarding School Malang - Thathit Manon Andini; Aini Alifatin; Dini Kurniawati; Retno Firdiyanti; Nur Hayatin (Universitas Muhammadiyah Malang, 2024)
Law No. 14 of 2005 concerning Teachers and Lecturers article 10 mandates that every teacher is required to meet the academic qualifications and teacher competencies that apply nationally, so that coaching to increase teacher competency needs to always receive more attention in its development. This service aims to increase teacher professionalism through innovative, creative and effective learning. This service was carried out at SMA Aisyiyah Boarding School Malang (SMA ABSM) in October 2022. The activity was attended by 13 teachers from various subjects. The methods used are two-way communication methods, lectures and training. This activity provides an explanation to teachers about strengthening teacher competency to become quality teachers and outstanding performance. This activity trains teachers in terms of pedagogical, professional, social and personal skills, and also equips teachers on how to be interesting when teaching and liked by their students, thereby creating innovative, creative and effective learning. This community service only reaches the stage of delivering material, and not yet at the stage of evaluating and assisting teachers in daily practice. Therefore, in the future it is hoped that there will be community service activities that focus on assisting teachers' daily practices, teaching practice, and reflecting together.